PENANAMAN NILAI-NILAI AKHLAKUL KARIMAH DALAM PEMBELAJARAN PAI DI MTS MU’ALLIMIN NU KOTA MALANG - Much Ilham Muttaqin; Fita Mustafida; Adi Sudrajat (VICRATINA, 2022)
MTs Mu'allimin NU is one of the schools located in Malang City. In carrying out teaching and learning activities, there are some unique things that need to be developed. Some of the uniqueness that was found was that there were several activities aimed at instilling moral values. In this study there are two research focuses, namely: first, what are the moral values that are instilled in MTs MU'ALLIMIN NU Malang City, second, How is the cultivation of morality in Islamic education learning at MTs MU'ALLIMIN NU Malang City. This study aims to find out what are the moral values that are instilled in MTs MU'ALLIMIN NU Malang City, second, to know the cultivation of morality in Islamic education learning at MTs MU'ALLIMIN NU Malang City. This research uses a qualitative approach and type of case study research. Data collection methods used are perception, meetings and documentation. The information examination procedure in this study incorporates four phases, in particular; information assortment, information buildup, information show and reaching determinations. Checking the validity of the data is done using the criteria of credibility, transferability, dependability, confirmability. The moral values instilled in MTs MU'ALLIMIN NU Malang City are divided into three aspects, Morals towards Allah SWT, Morals towards fellow humans, Morals towards nature and the environment. The cultivation of Akhlakul Karimah in Islamic Education Learning at MTs MU'ALLIMIN NU Malang City is carried out in learning on religious subjects. Where to get used to applying the material learned in class while applying the Uswah and Habituation Methods to instill morality in students.